2001
DOI: 10.1007/bf02762122
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteriovenous malformations

Abstract: Pulmonary arteriovenous malformations rarely present in childhood. Two cases are presented in this report. Both the cases presented clinically with cyanosis and clubbing without a cardiac murmur. The second case had cerebral abscess in addition. Both the cases underwent a contrast-enhanced echocardiography which suggested the presence of pulmonary arteriovenous malformations. The first case also underwent 99mTc radionuclide scan and pulmonary angiography. The cases are being reported for their characteristic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…Similar to this study, Tullu et al too did not find any significant difference in mortality related to mode of infection in the study conducted in 2000; however, in the 2005 study, mortality was significantly higher among postinjury tetanus cases. 3 7 Both prolonged spasms and shorter incubation period were not found to be associated with higher mortality. Similar findings were observed by Angurana et al 9 Singh and Seth found both these factors to significantly increase mortality.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Similar to this study, Tullu et al too did not find any significant difference in mortality related to mode of infection in the study conducted in 2000; however, in the 2005 study, mortality was significantly higher among postinjury tetanus cases. 3 7 Both prolonged spasms and shorter incubation period were not found to be associated with higher mortality. Similar findings were observed by Angurana et al 9 Singh and Seth found both these factors to significantly increase mortality.…”
Section: Discussionmentioning
confidence: 95%
“…9 Tullu et al treated all tetanus patients with 2,000 IU HTIG intramuscularly and intravenous crystalline penicillin. 7 Sedation was decided depending on modified Patel and Joag severity score: mild—diazepam 20 mg/kg/d, moderate—diazepam 40 mg/kg/d and chlorpromazine 0.5 mg/kg/dose qid, and severe—diazepam 60 mg/kg/d, chlorpromazine 0.5 mg/kg/dose qid, and phenobarbitone 5 mg/kg/d. 7 Pancuronium was used for patients with refractory spasms not controlled with the above drugs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations